Assessment of Changes in Toll Fares in Conditions of Increased Traffic Load - A. U. Talavirya; M. B. Laskin (Статистика и экономика)
The purpose of the study is to assess changes of toll fares used on toll collection points. When toll road is operating in an urban environment, the operator is inevitably faced with the need to adapt intelligent transport system to the conditions of an ever-increasing volume and changing composition of the traffic. Such changes have a direct impact on the capacity of the toll road, in particular at toll collection points. The conducted research is aimed at analyzing the method of reducing the traffic load at the toll collection points during peak hours by making changes to the toll fares aimed at uniform distribution of traffic flow throughout the day. As an example, a toll collection point on the main road direction of the Western High-Speed Diameter toll road was chosen.Materials and methods. A discrete-event simulation model developed in the AnyLogic software was used to assess the quality of operation and throughput of the toll collection point. The software has a sufficient level of detail to reproduce the operation of the toll collection system, and allows managing all the necessary parameters of the system and traffic flow. Analysis of the data obtained from the simulated model experiments was carried out using the statistical package R. Results. As part of the study, the operational characteristics of the toll collection point, in particular its threshold capacity, were determined, and, if it was exceeded, the length of the emerging queue was determined. Taking into account the operator’s risks arising from the formation of a traffic congestion, an approach was proposed to change the toll fare policy of the toll road by using a more flexible fares based on dividing the day time fare into several time intervals and using increasing coefficients for toll fare when paying for travel during peak hours. Using the example of toll booth of the Western High-Speed Diameter, the increasing coefficients of the cost of travel at a rush hour were considered, and the risks of reducing the operator’s income from toll collection were assessed.Conclusion. Based on the results obtained, an assessment of the effectiveness of the application of measures to change the existing toll fare policy, aimed at optimizing the traffic flow of a toll road, can be carried out. In addition, such an analysis can be used to assess the investment attractiveness of a project, develop a toll fare policy, increase income and other similar tasks. Further research can be aimed at increasing the economic indicators of toll road projects, and developing additional mathematical tools used in the formation of toll fare policy.